Aplicação de extratos de algas marinhas em cafeeiro sob deficiência hídrica e estresse salino - Bettini, Marcos de Oliveira [UNESP] (2015)
The effects of two seaweed extract were evaluated in terms of biometric characteristics, water relations, gas exchange and biochemical parameters for two coffee cultivars (Obatã e Catuaí 99). In order to have a better understanding how these products interfere in drought and salt stress tolerance. Two greenhouse trials arranged in randomized blocks with three replications per treatment were conducted with coffee transplants in 5 L pots under drip irrigation. The first drought stress experiment compared three irrigation levels (25%, 50% and 100% of water demand) in both coffee cultivars with two different seaweed extracts treatments and control. This experiment received three drought stress cycles of fifteen days interspersed with two periods of fifteen days of reconditioning. The second salt stress experiment induced with NaCL used same cultivars and seaweed extracts treatments in the first trial. In this case two salt stress cycles of thirty days interspersed with one thirty day period for reconditioning were applied. Seaweed extracts treatments were: A1 - Weekly Applications of diluted Ascophyllum nodosum soluble liquid extract. A2 - One combined application of Ascophyllum nodosum and Lithothamnium calcareum solid extracts. Water deficiency and salt stress treatments presented lower foliar water potential, net photosynthesis, transpiration and leaf area for both cultivars. Seaweed extracts application induced salt and drought stress tolerance. Coffee plants treated with seaweed extracts presented higher leaf area, root weight, stem water potential, carbon assimilation, lower rate Na+/K+, and changes in antioxidant enzymes activities.